Emerging Competencies in the Service Sector of Esmeraldas Canton for Business Innovation - Arce Minda, Patricio Marcelo (2025)
In a context of technological transformation and globalization, emerging competencies are consolidating as critical factors for business adaptability and sustainability. This study analyzed their level of mastery in 150 public and private service sector companies in the Esmeraldas canton, considering the demands imposed by digitalization, automation, and post-pandemic socio-labor changes. Customer service, effective communication, and digital skills emerge as strategic capabilities to strengthen human capital, drive business innovation, and boost local employment. A quantitative, descriptive, and cross-sectional approach was used. Data collection was carried out through structured surveys, validated by experts, and applied across eleven sectoral categories. Statistical analysis was conducted using SPSS version 25. The results showed a high level of mastery in interpersonal competencies such as customer service (98%) and effective communication (96%), along with significant gaps in digital skills, foreign languages, and proactivity. Sectors such as gastronomy, logistics, and transportation exhibited greater deficiencies, while technology and financial services stood out in digital competencies. The disparity in competency development highlights the need for sector-specific training strategies that enhance both technical and transversal skills, which are fundamental for innovation and competitiveness in post-pandemic environments. Strengthening emerging competencies constitutes a strategic imperative to transform the service sector in Esmeraldas, projecting continuous training, digital transformation, and human talent management as essential pillars for business sustainability and territorial development.